Composition and Biological Activity of Picea pungens and Picea orientalis Seed and Cone Essential Oils. Issue 3 (22nd February 2017) - Wajs‐Bonikowska, Anna; Szoka, Łukasz; Karna, Ewa; Wiktorowska‐Owczarek, Anna; Sienkiewicz, Monika
Abstract : The increasing consumption of natural products lead us to discover and study new plant materials, such as conifer seeds and cones, which could be easily available from the forest industry as a waste material, for their potential uses. The chemical composition of the essential oils of Picea pungens and Picea orientalis was fully characterized by GC and GC/MS methods. Seed and cone oils of both tree species were composed mainly of monoterpene hydrocarbons, among which limonene, α ‐ and β ‐pinene were the major, but in different proportions in the examined conifer essential oils. The levorotary form of chiral monoterpene molecules was predominant over the dextrorotary form. The composition of oils from P . pungens seeds and cones was similar, while the hydrodistilled oils of P . orientalis seeds and cones differed from each other, mainly by a higher amount of oxygenated derivatives of monoterpenes and by other higher molar mass terpenes in seed oil. The essential oils showed mild antimicrobial action, however P . orientalis cone oil exhibited stronger antimicrobial properties against tested bacterial species than those of P . pungens . Effects of the tested cone essential oils on human skin fibroblasts and microvascular endothelial cells (HMEC‐1) were similar: in a concentration of 0 – 0.075 μl/ml the oils were rather safe for human skin fibroblasts and 0 – 0.005 μl/ml for HMEC‐1 cells. IC 50 value of Picea pungens oils was 0.115 μl/ml, while that of Picea orientalis was 0.105 μl/ml. The value of IC 50 of both oils were 0.035 μl/ml for HMEC‐1 cells. The strongest effect on cell viability had the oil from Picea orientalis cones, while on DNA synthesis the oil from Picea pungens cones. Abstract :